2017
DOI: 10.1371/journal.pone.0175757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body condition on influenza A virus infection dynamics in mallards following a secondary exposure

Abstract: Migratory waterfowl are often viewed as vehicles for the global spread of influenza A viruses (IAVs), with mallards (Anas platyrhynchos) implicated as particularly important reservoir hosts. The physical demands and energetic costs of migration have been shown to influence birds’ body condition; poorer body condition may suppress immune function and affect the course of IAV infection. Our study evaluated the impact of body condition on immune function and viral shedding dynamics in mallards naturally exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The timing of the lysis peak in our study might be associated with virus excretion (and potentially with host susceptibility), as all birds were excreting virus at day 3 and day 7 postprimary exposure. Lower haptoglobin concentrations after LPAIV exposure in primary-exposed laboratory mallards is in accordance to Dannemiller et al (2017), who also reported lower haptoglobin concentrations after LPAIV H4N6 inoculation in comparison to baseline concentrations in wild-type domestic mallards. However, it should be noted that these birds had been naturally exposed to LPAIV H9 prior to the onset of their study (Dannemiller et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The timing of the lysis peak in our study might be associated with virus excretion (and potentially with host susceptibility), as all birds were excreting virus at day 3 and day 7 postprimary exposure. Lower haptoglobin concentrations after LPAIV exposure in primary-exposed laboratory mallards is in accordance to Dannemiller et al (2017), who also reported lower haptoglobin concentrations after LPAIV H4N6 inoculation in comparison to baseline concentrations in wild-type domestic mallards. However, it should be noted that these birds had been naturally exposed to LPAIV H9 prior to the onset of their study (Dannemiller et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Lower haptoglobin concentrations after LPAIV exposure in primary-exposed laboratory mallards is in accordance to Dannemiller et al (2017), who also reported lower haptoglobin concentrations after LPAIV H4N6 inoculation in comparison to baseline concentrations in wild-type domestic mallards. However, it should be noted that these birds had been naturally exposed to LPAIV H9 prior to the onset of their study (Dannemiller et al, 2017). A decrease in haptoglobin concentrations after an immune challenge is also reported in other avian species (Mazur-Gonkowska et al, 2004;Troisi et al, 2007;Hegemann et al, 2013), as well as a fish species (Vinterstare et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…In ducks, influenza infection typically occurs in the intestine, and seroconversion does not always occur [47]. However, ducks can respond to influenza vaccines [50], and show some evidence of protection from re-infection by the same strain [5,6] and some hetero-subtypic protection [291,292,293]. Duck antibody responses appear to prevent re-infection with the same strain, and this may drive the diversity of influenza viral subtypes in the wild [294].…”
Section: Other Potential Mechanisms Of Influenza Disease Resistanmentioning
confidence: 99%
“…AIV prevalence is higher in young birds (Farnsworth et al 2012, Papp et al 2017) and usually higher males, but not always (Wallensten et al 2007). Young, immunologically naı ¨ve birds shed a higher amount of virus due to both age-specific susceptibility (Costa et al 2010) and the lack of humoral immunity (Jourdain et al 2010, Dannemiller et al 2017) such that differences in the spatial and temporal distribution of demographic classes may impact the distribution of AIV. Second, at the local scale, fecal/oral transmission among birds aggregated in one location and transmission from environmental reservoirs over longer timescales (VanDalen et al 2010) influences infection dynamics (Breban et al 2009, Fuller et al 2010, Farnsworth et al 2012, Belkhiria et al 2016, Papp et al 2017.…”
Section: Introductionmentioning
confidence: 99%